Variation in habitat selection by male Strix nebulosa (Great Gray Owls) across the diel cycle, data archive ... - Gura, Katherine B. (Dryad, 2025)
We used GPS tracking and remotely-sensed environmental data to evaluate whether breeding-season habitat selection by adult male Strix nebulosa (Great Gray Owls) (n = 19) varied across diel periods (dawn, day, dusk, and night). We focused specifically on male owls because their breeding habitat selection remains largely unknown despite the critical role they play as food provisioners. To address knowledge gaps related to nocturnal habitat, we also evaluated finer-scale, microhabitat selection by male owls at night. Generally, S. nebulosa are associated with mature forests for nesting and meadows for foraging. Yet, in our study, owls avoided herbaceous wetlands during the day but strongly selected them at dawn, dusk, and at night, indicating time-dependent habitat selection. Moreover, owls avoided dry meadows at all times of the day, suggesting that wet rather than xeric meadows are important for foraging. Owls also preferred nighttime microhabitats that facilitated foraging, such as those with presence of ... : Associated habitat data for used and available locations for GPS-tagged, adult male Strix nebulosa (Great Gray Owls) (n = 19) during the breeding season in northwestern Wyoming between 2018-2021. Used locations were actual GPS locations for owls. Available locations were generated within 95% Kernel Density Estimate (KDE) areas. Habitat attributes were derived from remotely-sensed environmental data and exracted to owl locations. A subset of these data include microhabitat attributes measured via on-the-ground surveys. These sites were selected via a stratified random sampling design, in which we selected approximately 30 nighttime used locations, but no more than one location used per night per individual. Paired availale sites were selected from within 95% KDE areas. ...